Integrasi Etika Bisnis dan Prinsip Syariah dalam Perdagangan Internasional - Rizky Padlan; M. Daffa Raihan Buulolo; Hizri Al Husein; Firdan; Dwita Sakuntala (Cahaya Ilmu Bangsa, 2025)
The application of business ethics and sharia principles is becoming increasingly crucial in international trade, especially for exports and imports in developing countries such as Indonesia. Engagement in global trade offers both opportunities and challenges in adopting sharia ethics and principles. This research uses a qualitative approach by relying on secondary data from official reports, academic studies, and media publications. The data was analyzed content-wise to identify patterns and key themes regarding the role of business ethics and sharia principles in international trade. The implementation of business ethics and sharia principles enhances trust, transparency, competitiveness and business sustainability. Enabling factors include supportive policies, corporate commitment and sharia compliance. The integration of business ethics and sharia principles provides significant benefits to Indonesia's economic growth, with policy recommendations to increase education and awareness about the importance of ethics and sharia in international business. Keywords: Business_Ethics, Shari_Principles, International_Trade, Exports, Imports